2017
DOI: 10.1155/2017/1579652
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine Prevents Root Dentine Mineral Loss and Fracture Caused by Calcium Hydroxide over Time

Abstract: Purpose. To evaluate the mineral ion loss of root dentine after treatment with 2% chlorhexidine solution (CHX) and to compare its yield and flexural strength (fs) after exposure to calcium hydroxide [Ca(OH)2]. Materials and Methods. Dentine bars (DB) were made from 90 roots of bovine incisors and randomized into three groups: GControl: distilled/deionized water (DDW), GNaOCl: 2.5% sodium hypochlorite + 17% EDTA, and GCHX: CHX + DDW. The release of phosphate (PO4) and calcium (Ca) ions was measured by spectroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The antibiotics unlikely affected hardness and showed greater antibacterial activity against facultative anaerobe 16 . However, the high concentration of antibiotic paste is harmful to the stem cells from apical papilla which have the ability to regenerate the dental pulp 17 , 18 . Therefore, the modifying antibiotic delivery by fibrin hydrogel has more advantages over the removing of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The antibiotics unlikely affected hardness and showed greater antibacterial activity against facultative anaerobe 16 . However, the high concentration of antibiotic paste is harmful to the stem cells from apical papilla which have the ability to regenerate the dental pulp 17 , 18 . Therefore, the modifying antibiotic delivery by fibrin hydrogel has more advantages over the removing of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that could affect the resin–dentin bond strength is the influence of endodontic irrigants on dentin inorganic content. Due to its cationic nature, CHX has a minimal effect on dentin mineral content by binding to anionic calcium carbonate in dentin hydroxyapetite, thus preventing dentin demineralisation [28, 29]. However, it has been shown that composite resin bond strength to sound or demineralised dentin was not significantly different [30], which less emphasise the effect of endodontic irrigants on dentin mineral content as a contributing factor to resin–dentin bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its cationic nature, CHX has a F I G U R E 2 Distribution of failure mode (adhesive, cohesive and mixed failures) in coronal dentin restored with traditional or bulk-fill resin composite after treatment with chlorhexidine (CHX), alexidine (ALX), octenidine dihydrochloride (OCT) and saline (control). minimal effect on dentin mineral content by binding to anionic calcium carbonate in dentin hydroxyapetite, thus preventing dentin demineralisation [28,29]. However, it has been shown that composite resin bond strength to sound or demineralised dentin was not significantly different [30], which less emphasise the effect of endodontic irrigants on dentin mineral content as a contributing factor to resin-dentin bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in the results may be correlated with the combined use of NaOCl and EDTA/RC Prep in previous studies, while no NaOCl was used in the present study (with the exception of group 6). A study by Ribeiro et al reported that NaOCl degrades the organic matrix of root dentin, whereas EDTA binds to the calcium and phosphate ions of the hydroxyapatite structure, which leads to decreased yield strength and increased fracture tendency (17). Sim et al reported that a high concentration of NaOCl reduces the physical strength of root dentin (18).…”
Section: Discussionmentioning
confidence: 99%